Analytical method development and validation for simultaneous estimation of monoammonium glycyrrhizinate and sennoside-B in polyherbal laxative tablet using RP-HPLC - Madhavi Patel; Shivangi Chauhan; Vishal Patel; Hardik Soni; Vikram Trivedi (SpringerOpen, 2021)
Abstract Background Standardization of polyherbal medicine though being the need of the hour is a toilsome task. Among the various methods employed for quality control and standardization of polyherbal medicine, phytochemical profiling is of utmost importance as it signifies the quality as well as efficacy of the medicine. The work was aimed to develop and validate a simple, quick, and accurate RP-HPLC technique for simultaneous assessment of monoammonium glycyrrhizinate and sennoside-B in a polyherbal laxative tablet. The phytomarkers were effectively quantified by RP-HPLC system on C18 analytical column using gradient mobile phase consisting of phosphate buffer to acetonitrile with the detector wavelength set at 254 nm. This developed method was validated by determination of parameters like accuracy, linearity, precision, limit of detection, and quantification as well as robustness according to ICH guidelines. Results Calibration curve of both phytomarkers showed excellent linear correlation coefficients. LOD and LOQ were also calculated by equation. Precision studies were carried out using intra-day and inter-day intervals and RSD values were found to be less than 2.00%. The method was found to be accurate, which was evident from 98.96 to 101.39% and 99.17 to 100.67% recovery of monoammonium glycyrrhizinate and sennoside-B, respectively, when the formulation was spiked with the respective phytomarkers. Conclusion The validated method can be employed as standardization tool for herbal formulations with accuracy and precision. The developed method will assist in maintaining the good quality and batch to batch uniformity of polyherbal formulations containing Yashtimadhu, Swarnpatri, and Aragvadha as active ingredients.